Ecofisiologia de arbóreas utilizadas em revegetação de áreas antropizadas no ecótono cerrado/ Amazônia - Leonel, Léo Vieira (2017)
In the search for comfort and capital, man has been shaping Planet Earth according to his needs, which has caused profound changes to the environment over time, leading to the degradation of many habitats and, consequently, the extinction of species of fauna and flora. However, in recent decades, efforts have been made to mitigate the damage caused to nature, making their actions more sustainable and, at the same time, focusing on recovering some of these previously disturbed habitats. To recover these environments, the most widely used technique is revegetation, a practice that consists of planting tree species, prioritizing species native to the region. However, of the many species used in forest restoration, some are difficult to adapt, which causes high mortality rates. Considering this problem, this research aimed to evaluate the ecophysiological behavior of trees used in revegetation of anthropized areas in the Cerrado/Amazon ecotone. The experiment was conducted in the municipality of Imperatriz, located in the southern region of Maranhão. The experimental design was a 3 x 2 x 2 factorial, with 5 replications. The experiment evaluated 3 factors related to tree species (pioneer, secondary and climax species), 2 planting factors (planting with hydrogel and without hydrogel) and 2 factors related to light (planting in full sun and shade). Thirty-two nuclei were installed, each nucleus was composed of 3 seedlings distributed in the different successional groups. A total of 96 seedlings were used, of which 32 were pioneers, 32 secondary and 32 climax. The ecophysiological parameters evaluated in the nursery showed statistical difference, and the results are related to the individual characteristics of each species, since all were under the same edaphoclimatic conditions. As for the data related to the field, the worst results were observed in the 3rd evaluation, which may have been influenced by the low rainfall occurred in the period. Among the species studied in the research, A. fraxinifolium was the one that presented the best phenotypic plasticity, which allowed it to adapt to the different conditions evaluated. Regarding soil conditioning, its use was more effective for the development of seedlings during the dry season and in areas with full sun. Ecophysiology proved to be an excellent tool in detecting possible stresses caused to seedlings when exposed to natural field conditions